The Development of a Reading Book on House Construction Civilization Based on Project-Based Learning to Improve Children's Social Intelligence Character - Ari Nugrahanta, Gregorius; Relita Vertikasari Sekarningrum, Hilary; Sherlyta Erlansa Putri, Brigita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
The present study discusses the need to improve social intelligence character in elementary schools, which has so far been limited to lecture-based methods and not integrated into formal learning. The study aims to develop a reading book on the civilization of building houses based on Project-Based Learning (PjBL) to foster children's social intelligence character. This research employs the ADDIE research and development (RnD) model, which follows five phases namely, analysis, design, development, implementation, and evaluation. The study was conducted in Kalasan, Yogyakarta. The research findings are that 1) the development of the reading book was successfully carried out in a structured manner according to the ADDIE stages, 2) the quality of the reading book falls into the